Sumber dan Kondisi Fisik Air Bersih dengan Kejadian Diare di wilayah Kerja Puskesmas X Kabupaten Pinrang - Lilis Widiastuty; Ranti Ekasari; Sukfitrianty Syahrir; Yudi Adnan (HIGIENE: Jurnal Kesehatan Lingkungan, 2020)
Diarrheal disease is a major public health problem, especially in Indonesia. There are several factors related to the incidence of diarrhea, which are an inadequate supply of clean water, water contaminated by feces, lack of sanitary facilities, unhygienic disposal of feces, personal hygiene and poor environment, and improper food preparation and storage. The purpose of this study was to determine the relationship between sources and physical conditions of clean water with the incidence of diarrhea in Puskesmas X, Pinrang Regency. This research was an analytic observational study with a Cross-Sectional Study approach. The sample were 133 households carried out by a simple random sampling technique. Data were collected by interviews and observations. The results showed that there was no relationship between clean water sources (p = 0.882) and physical conditions (p = 0.980) and the incidence of diarrhea in Puskesmas X. The community needs to pay attention to spacing, improve the condition of facilities and place dug wells that meet the requirements and provide counseling on the importance of maintaining the quality of clean water sources.Key Words: Clean Water Source, Physical Condition of Water, Diarrhea